An investigation into the contribution of food coping strategies to food availability and dietary intake of adult women living in farm worker households on Oranje farm in the Fouriesburg district (RSA) - Dr R Kruger (University of Pretoria, 2013)
Dissertation (MCom (Consumer Science))--University of Pretoria, 2010.